Synthesis, Characterization and Antituberculosis Activity of Biologically Nanostructured Zinc and Titanium Metal Compounds - Belwal, Savita; Kariveda, Sujana; Ramagiri, Saritha (Asian Journal of Chemistry, 2020)
Green chemistry was used to obtain nano-range sized titanium and zinc compounds from their macro-sizes by using an aqueous extract of horse gram (Macrotyloma uniflorum). Ultraviolet-visible (UV-vis) and Fourier-transform infrared (FTIR) spectrophotometers were employed for characterizing the nanoparticles of biosynthesized metal nanoparticles. Transmission electron microscopy (TEM) was used to analyse the reduced nanoparticles of Ti and Zn metals. Microdilution was employed to determine in vitro properties, such as effects of nanocomplex antimicrobials on Mycobacterium tuberculosis (MTB) H37RV strain. MTB strains isolated from patients with multidrug-resistant tuberculosis (MDR-TB) were resistant to first-line drugs. Novel synthesized nano-complexes exhibited potential antituberculosis activities. Titanium nanocomplexes exhibited the highest minimal inhibitory concentration (MIC) in comparison to zinc nanocomplex. In a cytotoxic study, an IC50 of 1000 μg/mL, for both Ti and Zn nanocomplexes, was reported, and thus, these complexes were non-toxic when compared to isoniazid.